Pengaruh Social Media Marketing, Fasilitas Live Music, dan Store Atmosphere terhadap Keputusan Pembelian melalui Brand Image sebagai Variabel Intervening (Studi pada Konsumen Kedai Kopi di Jepara) - Arif, Ahmad Syaiful; Sutono, Sutono; Faidah, Faridhatun (Jurnal Studi Manajemen Bisnis, 2024)
This study aims to analyze the influence of social media marketing, live music facilities and store atmosphere on purchasing decisions through brand image as an intervening variable. The object of research is a coffee shop in the city of Jepara. This type of research is quantitative research. The population in this study were consumers of coffee shops in Jepara whose number was unknown and the sample for this study was 150 respondents. The sampling technique in this study used non-probability sampling, namely purposive sampling. Data were analyzed using SEM AMOS 24 software. The results of this study were social media marketing had a positive and significant effect on purchasing decisions and brand image, live music facilities had a positive and significant effect on purchasing decisions and had a positive and insignificant effect on brand image, store atmosphere had a negative effect and not significant to the purchase decision and has a positive and significant effect on brand image, brand image has a positive and significant effect on purchasing decisions. brand image cannot mediate the influence between social media marketing and live music facilities and purchase decisions, brand image can mediate the influence between store atmosphere and purchase decisions.